Clinical effectiveness and safety of fingolimod in relapsing remitting multiple sclerosis in Western Iran - Ouspid, Elham (Neurosciences (Riyadh), 2018)
OBJECTIVES: To investigate the clinical effectiveness and safety of fingolimod in the western Iranian population. METHODS: This study was performed as a prospective observational study between March 2014 and October 2015. Sixty patients with relapsing remitting multiple sclerosis (RRMS) who were referred to the MS clinic of Imam Reza Hospital, which is affiliated with Kermanshah University of Medical Sciences, Iran, were treated with 0.5 mg oral fingolimod capsules once daily for 12 months. The outcomes were clinical and included the annualized relapse rate, expanded disability status scale (EDSS) change, proportion of relapse-free patient, and side effects. RESULTS: An 85% reduction in the annualized relapse rate compared with the baseline (from 1.8±1.35 to 0.27±0.58, p=0.001) was observed, and 76.66% of patients were free from relapse after the 12-month intervention. In addition, a significant reduction of EDSS was measured from 3.32 at baseline to 2.97 (p=0.001). The overall adverse events in our study were similar to those in previous studies. CONCLUSION: The present study confirms the effectiveness of fingolimod as a second-line therapy in western Iranian RRMS patients. Fingolimod side effects were generally mild and tolerable.